Ergonomic Intervention on the Stamping Process of Part Body Component Improved Work Quality and Satisfaction and Time Efficiency at the Stamping Plant Division of PT ADM Jakarta - Isna Oesman, Titin; Manuaba, A.; Adiputra, N.; Sutjana, D.P. (Udayana University, 2010)
Part body component of a car is the finished product component that is mainlyproduced by the big press machine. In the production process of part body component of acar in the stamping plant division, the manual task is performed by two operators to feedingthe material sheet into the big press machine simultaneously. After the knobs were pressedtogether, the big press machine started to stamp the material sheet and the outcoming productis taken by the next operator. This task is performed repeatedly until it is the last one.Manual and comprehensive task that combined with speed in operating the big press machinecause who muscular tension which at the end could cause muscular complaints and prematurefatigue, that could decrease production and productivity.The current study of ergonomic intervention on stamping process of part bodycomponent of car was conducted in order to determine whether ergonomic intervention couldimprove the work quality, satisfaction and time efficiency in the stamping process.The subjects of study were 10 persons that were taken randomly. It was designedexperimentally with treatment by subject design. The method of data collection was byquestionnaire distribution and direct measurement of subject’s condition, time of stampingprocess and work environment before and after intervention. The Shapiro Wilk test showedthat all of the data had normal distribution and was followed by t-paired for data of workquality, work satisfaction, time efficiency, and the environment data. The significance level isset at 5%.The research result showed that work quality was improved (muscular complaints wasdecreased by 6,65%, fatigue was decreased by 5,47% and work boredom was decreased by5,87%), work satisfaction was improved up to 6,43%, time efficiency of stamping processwas improved up to 10,7%, the production was improved up to 2,59% and productivity wasimproved up to 32,65% as well as company’s profit was increased up to 3,95%.Hence, the study concludes that ergonomic intervention in the production process ofpart body component of car in the stamping plant division could improve work quality, worksatisfaction and time efficiency.